Design of the Variable Stiffness Mechanism with Human-robot Interaction and Research on Optimal Hammering Trajectory - Zhang Xiaolei; Wu Yaguang (Jixie chuandong)
In order to enhance the operation capability of the robot end-effector and ensure the safety of human-robot interaction, a variable stiffness mechanism （VSM） with variable stiffness, energy storage, strong environmental adaptation, and safe human-robot interaction was proposed. Firstly, the principle of the mechanism to realize the variable stiffness function through the axial arrangement and interaction of multiple magnets was introduced, and several different stiffness modes were proposed. Then, the VSM was mounted on a 6-DOF robotic system to conduct a series of hammering collision experiments to demonstrate and analyze the excellent energy storage and adaptive capability of the VSM. In the meantime, relying on the robotic system, using Python software and finite element analysis, how to achieve the optimal hammering trajectory and the best hammering effect through the VSM was explored. Finally, the potential damage to the robot caused by conducting a hard crash test chamber and how to adjust the VSM stiffness to mitigate this type of damage were also analyzed. The results show that the presence of the VSM can absorb most of the impulsive forces transmitted to the robot during its low stiffness phase, thus effectively avoiding the damage caused by the robotic system when performing similar tasks.